Structure and process of the patient records computerization project in hospitals of Burundi - Munezero, Florence; Sossa, Charles J.; Nyandwi, Joseph; Bazira, Leodegal (International Journal Of Community Medicine And Public Health, 2021)
Background: The computerization of patient records is an essential catalyst for the hospital performance. In Burundi the first patient records were computerized in 2015. The objective of this study is to evaluate the implementation of this project in order to identify the challenges for its success. Methods: This is a descriptive cross-sectional study conducted in 11 hospitals. An assessment tool was used to collect data on the availability and organization of resources at the beginning of the project, on the process and on the completeness of patient records. The data collection was been done in February 2020. Results: The structure and process components were moderately satisfactory with mean scores of 53% and 51% respectively. Governance (21%) for structure component, and maintenance (44%) for process component were the elements with the lowest scores. Concerning the completeness of the records, the main diagnosis at discharge was completed for 68% of the records in the gynecological-obstetrical consultation service; 58% for the pediatric service; 55% for the adult consultation service and 28% for the emergency service. Hospitals that were computerized in 2015 compared to 2017 (OR: 12.5 [10.9 -14.4]) and district hospitals compared to regional and national hospitals (OR: 22.1 [19.3 -25.2]) were more likely to have patient records with diagnosis at discharge. Conclusions: Continued mobilization of resources, making available the guidelines for managing the electronic patient record and implementing strategies to strengthen the capacity of users will ensure the sustainability of the patient record computerization project.